EFEKTIVITAS PENERAPAN MULTIMEDIA INTERAKTIF DALAM PENILAIAN KETERAMPILAN 4C PADA PEMBELAJARAN FISIKA: STUDI LITERATURE - Putri, Fina Afriani; Mufit, Fatni (EduFisika: Jurnal Pendidikan Fisika, 2023)
This research aims to analyze the effectiveness of implementing interactive multimedia in assessing 4C skills in physics learning. This effectiveness is evaluated from the 4C skills (Critical thinking, Creativity, Collaboration, and Communication). This research was conducted because there are still many physics lessons that prioritize mastery of concepts only, which causes a lack of interest in students' learning. Therefore, interactive multimedia is needed, which can make students more enthusiastic about participating in learning through pictures, videos, and moving animations. The method used is a literature study with a quantitative approach. This research is limited to the effect of using interactive multimedia on physics material at the elementary, middle school, high school, and university levels. Researchers obtained 20 references from 2012-2022 from Sinta, Google Scholar, Garuda, and others. From the analysis of the literature study that has been carried out, it is concluded that interactive multimedia significantly influences the assessment of 4C skills (Critical thinking, Creativity, Collaboration, and Communication). The significant influence is on critical thinking skills.